OP34 Online care for sexually transmitted infections: using qualitative research in intervention development and evaluation. (13th September 2016) - Aicken, CRH; Fuller, SS; Sutcliffe, LJ; Gibbs, J; Tickle, L; Estcourt, CS; Sonnenberg, P; Mercer, CH; Johnson, AM; Sadiq, ST; Shahmanesh, M
Abstract : Background: Sexually transmitted infections (STI) remain a major public health problem, despite widespread provision of STI testing and treatment through clinical services and chlamydia screening for young people in England. Early detection and treatment of these often asymptomatic infections is vital, but barriers to testing include embarrassment, privacy concerns, and inconvenience. Diagnostic technologies, which potentially enable STI self-testing within online care-pathways to treatment, are being developed; people could self-test and receive diagnoses and treatment 'remote' from health services, perhaps without interacting with health-professionals. Within a programme of research to develop this complex intervention, we qualitatively explored views and experiences, to inform its development and understand its acceptability. Methods: In-depth interview study, with two phases (P1, P2). P1 explored, hypothetically, the acceptability of online care-pathways including STI self-testing, among 25 purposively-sampled college students, aged 16–24. P1's findings informed development of the Online Chlamydia Pathway (OCP), which included an automated online consultation, treatment collection from community pharmacy, and a helpline for support and to facilitate clinic access where appropriate. P2: People diagnosed (following conventional testing) with chlamydia, were offered the OCP in an exploratory study. Interviews explored views and experiences of 40 purposively-sampled OCP users. Thematic analyses, using 'Framework' was used for data management. Results: P1: 16 men and 9 women participated. Themes about speed, convenience and privacy (avoiding face-to-face consultations, concealing sexual healthcare use) were identified. Self-testing within online care-pathways was discussed as more convenient, private and quicker than existing services. Interviewees expressed concern about electronic 'evidence' of sexual healthcare use, and self-operation of novel technology. They valued the option of support from health-professionals. Association with NHS services conveyed trustworthiness. In response to these findings, the OCP was delivered as a web-app, text-messages were worded discreetly, NHS logos displayed, and a helpline and facilitated clinic access were included. P2: 19 men and 21 women, aged 18–35, participated. Themes about speed, convenience and privacy were further developed, but some described how these perceived advantages were compromised when they collected treatment in pharmacies. Interviewees expressed few, minor concerns about internet/'technological' privacy risks, and appreciated the OCP's association with existing NHS services. They favoured the helpline's presence, those using it gaining reassurance. Conclusion: This novel intervention's ongoing development has been iteratively informed by qualitative research. Although it was perceived as an acceptable alternative to conventional sexual healthcare, linkage with existing services and optional human support remained important. Further research is needed regarding other risk groups and infections, and the future self-test.